Prevalence of dental caries and influence factors among students in Beijing: A cross-sectional study. - Youhan Wen; Yu Liu; Ning Ning; Huiyu Xu; Jingshu Zhang; Hai Zhao; Ran Qin; Lu Wang; Xin Guo; Liyuan Tao (PLoS ONE)
Background The burden of dental caries continues to be substantial worldwide, significantly affecting adolescents and children's growth and quality of life. This study aimed to explore the epidemiological characteristics of dental caries and examine influencing factors that contribute to caries among children and adolescents in Beijing. Methods A total of 21,403 students (average age 12.8 ± 2.5 years old) were included in this cross-sectional survey. The DMFT/dmft index (decayed (D), missing (M), and filled (F) teeth) was used for screening. Multistage stratified random cluster sampling methods were conducted in primary and secondary schools in Beijing in 2021. Data were collected using questionnaires and assessed using a logistic regression analysis. Statistical significance was set at P < 0.05. Result The overall prevalence of caries was 40.5% (95% CI: 39.8-41.1%). The mean score of DMFT was 1.31 ± 2.11, and the mean score of dmft was 0.39 ± 1.24. Among participants, girls, students in lower grades, those of younger ages, and those with lower BMI levels were more likely to experience dental caries. A multivariate logistic regression analysis identified the following variables as predictors of an increased risk for caries experience: residing in boarding school (odds ratio [OR]=1.15); coming from a rural area (OR = 2.55); frequent consumption of sugary beverages (ORmax = 1.23), and fresh fruit (ORmax = 1.35); breakfast irregularity (ORmax = 1.22); infrequent tooth brushing (ORmax = 1.16); and longer sleep duration (ORmax = 1.30). Conclusions Dental caries, widely prevalent among children and adolescents in Beijing, is associated with dietary habits, hygiene practices, and sleep patterns. To effectively mitigate its burden, prevention strategies targeting these identified risk factors should be prioritized.